System gwarancji roszczeń ubezpieczeniowych w Stanach Zjednoczonych - Janusz, Alicja (Guarantee Scheme for Insurance Claims in the USA, 2008)
The main concept of creating guarantee schemes for insurance claims in case of an insurance company declaring insolvency is to protect the owners of insurance policies and as a consequence to preserve public trust in the insurance sector. The institutionalized form of these schemes become insurance guarantee schemes which are entitled to take over and pay out due claims to clients of insurance companies which have declared insolvency. The functioning of such institutions is not common in European countries. The situation, however, may change as a result of proposals to intro-duce homogenous national regulations in the discussed domain, which will be practically expressed by means of a new directive regarding insurance guarantee schemes. The USA is the country which, as first, constructed the guarantee scheme for insurance claims and therefore offers the most extensive experience in this area. The hereby paper analyses the principles of the above scheme functioning by pointing to its architecture, guarantee scope, and sources of its functioning.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1197, s. 105-111